Breach rhythm may be suppressed as a form of Todd's paralysis - Lyudmilov, Cristina; Petersone, Daina; Schmidt, Christian; Bösel, Julian; Rösche, Johannes (Journal of clinical neurophysiology, 2020)
This case report will provide further evidence for the fact that breach rhythm is not the effect of a bone abnormality only. We present the case of an 84-year-old woman, who had a craniotomy 14 month before admission to our emergency department with a focal inhibitory status epilepticus. Even after clinical recovery, electroencephalography revealed frequent subclinical seizure patterns. When seizure activity was suppressed by anticonvulsive medication with levetiracetam, breach rhythm appeared. Breach rhythm develops usually some months after craniotomy and therefore should have been established in our patient at the time of admission. Therefore, it is reasonable to assume that it was in some way suppressed by the seizure activity in our primary EEG recordings. The appearance of the breach rhythm after the complete suppression of seizure activity by antiepileptic drug treatment shows that breach rhythm is not purely the result of a skull defect but is related to the functional state of the brain tissue beneath.
Gesehen am 30.10.2020